2008
DOI: 10.1371/journal.pone.0002790
|View full text |Cite
|
Sign up to set email alerts
|

Extra-Nuclear Signaling of Progesterone Receptor to Breast Cancer Cell Movement and Invasion through the Actin Cytoskeleton

Abstract: Progesterone plays a role in breast cancer development and progression but the effects on breast cancer cell movement or invasion have not been fully explored. In this study, we investigate the actions of natural progesterone and of the synthetic progestin medroxyprogesterone acetate (MPA) on actin cytoskeleton remodeling and on breast cancer cell movement and invasion. In particular, we characterize the nongenomic signaling cascades implicated in these actions. T47-D breast cancer cells display enhanced horiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
64
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 52 publications
11
64
0
Order By: Relevance
“…As such, these proteins might have the potential to be putative breast cancer markers. As expected, some well-known breast cancer markers, such as 14-3-3 proteins (Danes et al, 2008), annexins (Cao et al, 2008a), calmodulin (Gallo et al, 2008), anterior gradient homolog 2 (AGR-2) (Zweitzig et al, 2007;Fritzsche et al, 2006), Galectin-1 (Jung et al, 2007) and Rho-associated protein kinase-2 (ROCK2) (Fu et al, 2008b), were also identified in this 2D-DIGE experiment, lending credence to the reliability of early phase biomarker detection using this experimental strategy. Fig.…”
Section: D-dige and Maldi-tof Ms Analysis Of Total Intracellular Prosupporting
confidence: 78%
“…As such, these proteins might have the potential to be putative breast cancer markers. As expected, some well-known breast cancer markers, such as 14-3-3 proteins (Danes et al, 2008), annexins (Cao et al, 2008a), calmodulin (Gallo et al, 2008), anterior gradient homolog 2 (AGR-2) (Zweitzig et al, 2007;Fritzsche et al, 2006), Galectin-1 (Jung et al, 2007) and Rho-associated protein kinase-2 (ROCK2) (Fu et al, 2008b), were also identified in this 2D-DIGE experiment, lending credence to the reliability of early phase biomarker detection using this experimental strategy. Fig.…”
Section: D-dige and Maldi-tof Ms Analysis Of Total Intracellular Prosupporting
confidence: 78%
“…Caveolins are membrane proteins involved in receptor-independent endocytosis and can be upregulated during epithelial-to-mesenchymal transition (Bailey and Liu, 2008). Moesin, a member of the ezrin/radixin/moesin family of actinbinding proteins, cross-links the actin cytoskeleton to the plasma membrane (Rosenblatt, 2008) and recent data suggest that cell movement through rapid actin cytoskeleton remodelling is mediated by moesin activation (Fu et al, 2008). Thus, high expression of these two markers that are involved in cell adhesion and migration may characterise a cell phenotype that is particularly susceptible to Src inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The small GTPase RhoA and its downstream effector ROCK-2 play a central role in regulating the actin cytoskeleton by delivering upstream signaling events to actin-regulatory proteins such as moesin or FAK (Torsoni et al 2005, Fu et al 2008b). Treatment of T47-D cells with progesterone increased the amount of active, GTP-bound RhoA (Fig.…”
Section: Pr Signaling To Fak: Role Of Rhoa and Rock-2mentioning
confidence: 99%